Reduced gait speed in hospitalized older adults: associated sociodemographic and mobility characteristics - Danielle Bordin; Lorena Cruziniani Zubek; Giovana Aparecida Santos; Pamela Tainá Licoviski; Midiã Vanessa dos Santos Spekalski (Fisioterapia e Pesquisa)
ABSTRACT This study aims to evaluate the predominance of reduced gait speed in hospitalized older people and to verify the association with demographic and mobility factors. This is a cross-sectional, quantitative study conducted with older adults from a teaching hospital in Paraná (2020–2021) (n=662). Sociodemographic and health questionnaires were applied, as well as the Clinical-Functional Vulnerability Index (CFVI-20). The Chi-square test was employed. Most participants were men (51.8%), aged from 60 to 69 years (49.2%), married (47.9%), retired or pensioners (69.5%), and with low education level (31.3%). Reduced gait speed was present in 37.61% of the older adults and associated with: age <70 years (p=0.003); non-exercise of work activity (p=0.045); inability to raise arms above shoulders (p=0.05) and handle and hold small objects (p=0.011); and having stopped using the mobile phone (p<0.001) and bathing alone (p=0.001) due to health. It is concluded that the predominance of older people with reduced gait speed was high, associated with the demographic characteristics of advanced age and non-exercise of labor activity. Regarding mobility factors, all the older adults showed an association with reduced gait speed.